Pathogenic role of glycan-specific IgG antibodies in IgA nephropathy - Yan-feng Zhao (BMC Nephrology, 2017)
Abstract Background Accumulating evidences proved the important roles of circulating IgA1-containing immune complexes (cIgA1) in IgA nephropathy (IgAN). Galactose-deficient IgA1 (Gd-IgA1) and glycan-specific IgG antibody have been identified as major components in cIgA1. Before, Gd-IgA1 was reported as a vital factor in IgAN, partly via of its pathogenic role to induce mesangial cells activation. However, we still lack direct evidences to clarify the biological effect of glycan-specific IgG antibody in IgAN. Methods In the present study, we enrolled 35 IgAN patients and 17 age- and sex-matched healthy controls. Using uniform aberrant glycosylated IgA1 molecules, and IgG from different individuals, we in vitro prepared IgG-ddIgA1 complexes, and compared the biological differences among these immune complexes regarding their proliferative and inflammatory effects on mesangial cells. Results IgG-ddIgA1 complexes from both patients with IgA nephropathy (IgAN-IgG-dd-IgA1) and healthy controls (HC-IgG-dd-IgA1) could induce the proliferation of mesangial cells and up-regulate expression of MCP-1, IL-6 and CXCL1. The levels of mesangial cells proliferation induced by IgAN-IgG-dd-IgA1 were significantly higher than those induced by HC-IgG-dd-IgA1 (1.10 ± 0.05 vs. 1.03 ± 0.03; p < 0.001). However, the levels of secreted MCP-1, IL-6 and CXCL1 from mesangial cells challenged by IgAN-IgG-dd-IgA1 and HC-IgG-dd-IgA1 were comparable. Conclusions We found that glycan-specific IgG antibodies derived from patients with IgAN had the biological effect to induce mesangial cells proliferation. Moreover, in the present study we also established a method for in vitro preparation of pathogenic IgG-ddIgA1 complexes, which could be applied in future studies exploring IgAN pathogenesis.